Gp350-anchored extracellular vesicles: promising vehicles for delivering therapeutic drugs of B cell malignancies - Huiqing Xiu; Xi Nan; Danfeng Guo; Jiaoli Wang; Jiahui Li; Yanmei Peng; Guirun Xiong; Shibo Wang; Changjun Wang; Gensheng Zhang; Yunshan Yang; Zhijian Cai (Elsevier, 2022)
Although chimeric antigen receptor-modified (CAR) T cell therapy has been successfully applied in the treatment of acute B lymphocytic leukemia, its effect on Burkitt lymphoma (BL) and chronic B lymphocytic leukemia (B-CLL) is unsatisfactory. Moreover, fatal side effects greatly impede CAR T cell application. Extracellular vesicles (EVs) are excellent carriers of therapeutic agents. Nevertheless, EVs mainly accumulate in the liver when administered without modification. As an envelope glycoprotein of Epstein-Barr viruses, gp350 can efficiently bind CD21 on B cells. Here, gp350 was directly anchored onto red blood cell EVs (RBC-EVs) via its transmembrane region combined with low-voltage electroporation. The results showed that gp350 could anchor to RBC-EVs with high efficiency and that the resulting gp350-anchored RBC-EVs (RBC-EVs/gp350Etp) exhibited increased targeting to CD21+ BL and B-CLL relative to RBC-EVs. After the loading of doxorubicin or fludarabine, RBC-EVs/gp350Etp had powerful cytotoxicity and therapeutic efficacy on CD21+ BL or B-CLL, respectively. Moreover, RBC-EVs/gp350Etp loaded with a drug did not exhibit any apparent systemic toxicity and specifically induced the apoptosis of tumor B cells but not normal B cells. Therefore, our findings indicate that drug-loaded RBC-EVs/gp350Etp may be adopted in the treatment of CD21+ B cell malignancies.